(untitled) (Journal of Enam Medical College, 2012)
Background: Preterm birth is the primary cause of perinatal mortality and morbidity. Recently, it has become a significant issue in public health policies of developing countries. Among the various causes, pregnancy induced hypertension (PIH) and Gestational diabetes mellitus (GDM) are two important high-risk factors for preterm birth. Again, placenta is a mirror that reflects the well-being of the fetus and continuously undergoes a change in weight, structure, shape and function in order to support the well-being of the fetus. Objective: To make an in-depth analysis on the possible gross morphological changes in preterm placenta in respect of GDM and PIH. Materials and Methods: The study was observational, analytical and cross sectional. The patients under this study were selected from the Obstetric ward of BSMMU and BIRDEM Hospital, from June 2005 to October 2005. A total of sixty-six samples were collected from women during 28 weeks to 36 completed weeks of gestation. Among them, twenty-two samples were from mothers having GDM, twenty-two having PIH and twenty-two belonged to normal pregnancy (control group). The placentas were examined to measure their diameter, thickness, cotyledons number, weight, and volume. Results: In this study, the GDM group showed significantly higher values for the variables of diameter, weight, volume and number of cotyledons as compared to PIH group. On the other hand, the thickness of the placenta showed lower values in GDM group, but the result did not reach a significant level. Conclusion: From the findings of this study, it is difficult to establish a clear-cut correlation about placental changes in diabetic and hypertensive mothers during pregnancy. However, the changes in placental weight, volume and diameter found in gestational diabetic mother may be a long term compensatory mechanism, aiming to secure a sufficient nutrient supply to support the growth of the foetus. So, postnatal examination of the placenta can yield information that may be important for immediate and late management of the mother and neonate. DOI: http://dx.doi.org/10.3329/jemc.v1i2.11466 J Enam Med Col 2011; 1(2): 71-75